Evaluation of phytochemical and pharmacological activities of Taraxacum syriacum and Alchemilla arvensis - Ali, Hazar; Alkowni, Raed; Jaradat, Nidal; Masri, Motasem (Jordan Journal of Pharmaceutical Sciences, 2021)
Oxidative stress, obesity, and multidrug resistance to pathogenic microorganisms are major challenges in the health care systems and pharmaceutical industries that prompt scientists to search for alternative sources with maximum efficacy and few side effects. Therefore, this study aimed to screen phytoconstituents, and estimate total phenols, flavonoids contents, antioxidant, antilipase, and antimicrobial activities of two selected plants, Taraxacum syriacum and Alchemilla arvensis four extracts. Conventional phytochemical assays were utilized for qualitative and quantitative determinations of the major phytochemical classes, total phenol, and flavonoids contents of methanol, hexane, acetone, and water extracts of both plants. While the antioxidant activity was evaluated using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay. In addition, the antilipase activity was conducted using the porcine pancreatic lipase inhibitory test which was conducted by using a UV-visible spectrophotometer. Moreover, the antimicrobial activity of both plants’ four extracts was established utilizing agar diffusion and micro-broth dilution methods against six microbial strains. The results revealed that the highest total phenol content was observed in the T. syriacum acetone extract (272.0 mg gallic acidE/g), while the highest total flavonoid content was detected in A. arvensis methanolic extract (83.3 mg rutinE/g). Actually, T. syriacum water extract has the best antioxidant potential among other extracts with an IC50 value of 95.5 µg/ml while A. arvensis acetone extract has the best antioxidant activity among other plant extracts with an IC50 dose of 4.9 µg/ml. Regarding antilipase activity, A. arvensis water extract showed a potent porcine pancreatic lipase inhibitory effect with an IC50 value of 21.4 µg/ml. However, most of the evaluated T. syriacum and A. arvensis plants’ extracts showed broad-spectrum antibacterial and antifungal activities. This study recommended targeting these potentially medicinal plants in antioxidants and anticipate drugs for further in-vivo and preclinical studies.